Quantification of malaria antigens PfHRP2 and pLDH by quantitative suspension array technology in whole blood, dried blood spot and plasma (2020)
ABSTRACT: Background: Malaria diagnostics by rapid diagnostic test (RDT) relies primarily on the qualitative detection of Plasmodium falciparum histidine-rich protein 2 (PfHRP2) and Plasmodium spp lactate dehydrogenase (pLDH). As novel RDTs with increased sensitivity are being developed and implemented as point of care diagnostics, highly sensitive laboratory-based assays are needed for evaluating RDT performance. Here, a quantitative suspension array technology (qSAT) was developed, validated and applied for the simultaneous detection of PfHRP2 and pLDH in a variety of biological samples (whole blood, plasma and dried blood spots) from individuals living in different endemic countries. Results: The qSAT was specific for the target antigens, with analytical ranges of 6.8 to 762.8 pg/ml for PfHRP2 and 78.1 to 17076.6 pg/ml for P. falciparum LDH (Pf-LDH). The assay detected Plasmodium vivax LDH (Pv-LDH) at a lower sensitivity than Pf-LDH (analytical range of 1093.20 to 187288.5 pg/ml). Both PfHRP2 and pLDH levels determined using the qSAT showed to positively correlate with parasite densities determined by quantitative PCR (Spearman r = 0.59 and 0.75, respectively) as well as microscopy (Spearman r = 0.40 and 0.75, respectively), suggesting the assay to be a good predictor of parasite density. Conclusion: This immunoassay can be used as a reference test for the detection and quantification of PfHRP2 and pLDH, and could serve for external validation of RDT performance, to determine antigen persistence after parasite clearance, as well as a complementary tool to assess malaria burden in endemic settings. Keywords: Histidine-rich protein 2; Luminex; Malaria; Parasite lactate dehydrogenase; Quantitative suspension array technology; Rapid diagnostic test.